ANALISIS KINERJA KEUANGAN BANK RAKYAT INDONESIA SEBELUM DAN SELAMA MASA PANDEMI COVID – 19 : STUDI KOMPARATIF - Achyat Budianto; Ferri Saputra Tanjung; Marnas Marnas; Beid Fitrianova Andriani; A. Rozi (Politeknik Negeri Ambon, 2023)
This study aims to examine the differences in the financial performance of PT Bank Rakyat Indonesia before and during the COVID-19 pandemic. This test uses a quantitative approach, and the data samples used from the third quarter of 2017 to the second quarter of 2022 are 20 samples. Bank Rakyat Indonesia, as the research object, has the most customers among other banks. Testing was carried out using the paired sample t-test method. The results of the study show differences in financial performance before and during the COVID-19 pandemic in the ratios of NPL, ROA, ROE, and LDR, but there is no difference in financial performance before or during the COVID-19 pandemic in the BOPO ratio